Pediatric both Bone Forearm Fractures Fixed with Titanium Elastic Nails (TENs) - RC, Dhirgha Raj; KC, Kapil Mani; Acharya, Parimal; Pangeni, Bandhuram (Nepal Orthopaedic Association Journal, 2016)
BACKGROUND: Pediatric forearm fractures are usually managed by conservative methods, however, non-operative treatment is not suitable for displaced unstable diaphyseal fractures which require surgical intervention. Non-operative treatment may lead to significant angular and rotational deformity which is rarely corrected if the children 8years. Different surgical techniques are available including plating and intramedullary nailing. Among these titanium elastic nailing is one of the best options because of its several advantages over other techniques. METHODS: This is a prospective study which included 73 patients of age 4 to 14 years treated with titanium elastic nailing (TENs) following closed reduction or mini-open method if required. All the demographic profiles, techniques, indications of surgery, union time, functional outcomes and complications were evaluated during follow up examination. Final results were documented at the time of union of fracture. RESULTS: This study included 73 patients with unstable both bone forearm fractures with mean age of 9.90±2.28 years. There were 43 (58.9%) male, 30 (41.1%) female, forty-four (60.3%) of patients sustained fracture in middle shaft of forearm, 7 (9.6%) patients needed open reduction for nail fixation, 69 (94.5%) patients had excellent results according to Price et al criteria. Average time to unite the fracture was 9.10±1.81 weeks and 13.7% of patients had irritation and bursa formation over entry site, 6.8% had superficial radial nerve neuropraxia, 8.2% had delayed union and one patient had osteomyelitis. CONCLUSION: Titanium elastic intramedullary nailing is an appropriate, effective and safe operation for unstable diaphyseal fractures of the forearm in children who cannot be treated by closed manipulation.